SystemC Transaction-Level Modeling of an MPSoC Platform Based on an Open Source ISS by Using Interprocess Communication. (28th August 2008) - Boukhechem, Sami; Bourennane, El-Bay
Abstract : Transaction-level modeling (TLM) is a promising technique to deal with the increasing complexity of modern embedded systems. This model allows a system designer to model a complete application, composed of hardware and software parts, at several levels of abstraction. For this purpose, we use systemC, which is proposed as a standardized modeling language. This paper presents a transaction-level modeling cosimulation methodology for modeling, validating, and verifying our embedded open architecture platform. The proposed platform is an open source multiprocessor system-on-chip (MPSoC) platform, integrated under the synthesis tool for adaptive and reconfigurable system-on-chip (STARSoC) environment. It relies on the integration between an open source instruction set simulators (ISSs), OR1Ksim platform, and the systemC simulation environment which contains other components (wishbone bus, memories, …, etc.). The aim of this work is to provide designers with the possibility of faster and efficient architecture exploration at a higher level of abstractions, starting from an algorithmic description to implementation details.